UTILIZING MBSE PATTERNS TO ACCELERATE SYSTEM VERIFICATION. Issue 1 (6th April 2017) - Cook, David; Schindel, William D.
ABSTRACT: In aerospace, automotive, healthcare, and other domains, the capability to effectively plan and perform system verification tests is increasingly a strategic differentiator. This paper reports on methods used to improve effectiveness of complex aircraft system tests, the gains achieved, and their connection to underlying methods and trends. These include use of model‐based systems engineering (MBSE), leveraged by pattern‐based systems engineering (PBSE) to generate configurable, reusable system models — the focus of the INCOSE MBSE Patterns Challenge Team (Patterns Challenge Team 2013‐2015). Distinctive aspects include (1) use of configurable, model‐based patterns of system descriptions, including configurable system verification tests, (2) improved ability of model‐based descriptions to integrate modeling tools and automated systems for test management, (3) use of models to describe both the system under development and the development process, and (4) ability of these models to be integrated with other system lifecycle management processes and information systems, for increased leverage.